The utility of the Montreal Cognitive Assessment as a mental capacity assessment tool for patients with a learning disability. (18th December 2015) - Edge, Daniel; Oyefeso, Adenekan; Evans, Carys; Evans, Amber
Abstract : Accessible summary: Accurate assessment of a patient's mental capacity is important, yet out of the clinical assessments currently available, there does not appear to be sufficient accessible tools suitable for people with a learning disability. Incorrect assumptions are often made regarding the capacity of patients who have learning disabilities to make decisions about important aspects of their life. This preliminary study investigated whether or not it was possible to adapt a well‐known assessment of cognitive impairment (The Montreal Cognitive Assessment) and use this as a tool to determine capacity in patients with a learning disability. Abstract: Objective: To determine the psychometric properties of the Montreal Cognitive Assessment (MoCA) in patients with a learning disability and examine it's utility for conducting mental capacity assessment. Method: This study was a cross‐sectional, instrument validation study in an inpatient hospital setting, located in the East of England. The sample consisted of two groups: (i) 31 consecutively admitted hospital patients and (ii) 10 multidisciplinary team members who served as a comparison group. The MoCA, a 12‐item screen for mild cognitive impairment and the Dysexecutive Questionnaire (DEX), were used in this study. Item analysis was conducted by comparing item endorsement for all participants that had a learning disability utilising Difficulty and Discrimination Indices for each item on the MoCA. We examined the internal consistency of a revised scale derived from item analysis and used a one‐way ANOVA to determine concurrent validity by comparing scores between two patient subgroups and the comparison group. Results: A 7‐item scale, 'MoCA‐LD' (alpha coefficient = 0.82) emerged from item analysis. A statistically significant negative correlation was observed between MoCA‐LD and DEX (Pearson correlation = −0.66, P < 0.01). As expected, participants in the borderline category scored higher on MoCA‐LD than those with mild learning disability, as did those with no learning disability ( P < 0.001). Conclusion: The MoCA‐LD has the potential to be a useful tool for mental capacity assessment in patients with a learning disability.